Risk Factors for Survival After Heart Transplantation in Children and Young Adults: A 22-Year Study of 179 Transplants. Issue 5 (September 2018) - Shah, Shawn; Asante-Korang, Alfred; Ghazarian, Sharon R.; Stapleton, Gary; Herbert, Carrie; Decker, Jamie; Almodovar, Melvin C.; Karl, Tom R.; Do, Nhue L.; Quintessenza, James A.; Mavroudis, Constantine; Vricella, Luca A.; et al.
Background: This article reviews all patients who underwent heart transplantation (HTx) within a single institution (172 patients underwent 179 HTx [167 first-time HTxs, 10 second HTxs, 2 third HTxs]) to describe diagnostic characteristics, management protocols, and risk factors for mortality. Methods: Descriptive analysis was performed for the entire cohort using mean, standard deviation, median, interquartile range, and overall range, as appropriate. Univariable and multivariable Cox proportional hazards models were performed to identify prognostic factors for outcomes over time. The primary outcome of interest was mortality, which was modeled by Kaplan-Meier analysis. Results: Median age at HTx was 263 days (range, 5 days to 24 years; mean = 4.63 ± 5.95 years; 18 neonates, 79 infants). Median weight at HTx was 7.5 kg (range, 2.2-113 kg; mean = 19.36 ± 23.54). Diagnostic categories were cardiomyopathy (n = 62), primary transplantation for hypoplastic left heart syndrome (HLHS) or HLHS-related malformation (n = 33), transplantation after cardiac surgery for HLHS or HLHS-related malformation (n = 17), non-HLHS congenital heart disease (n = 55), and retransplant (n = 12). Operative mortality was 10.1% (18 patients). Cumulative total follow-up is 1, 355 years. Late mortality was 18.4% (33 patients). Overall Kaplan-Meier five-year survival was 76.2%. One hundred twenty-one patients are alive with a mean follow-up of 7.61 ± 6.46 years. No survival differences were seen among the five diagnostic subgroups ( P = .064) or between immunosensitized patients (n = 31) and nonimmunosensitized patients (n = 141; P = .422). Conclusions: Excellent results are expected for children undergoing HTx with comparable results among diagnostic groups. Pretransplant mechanical circulatory support and posttransplant mechanical circulatory support are risk factors for decreased survival. Survival after transplantation for HLHS or HLHS-related malformation is better with primary HTx in comparison to HTx after prior cardiac surgery.